2013
DOI: 10.1155/2013/530396
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Trend and Determinants of Breastfeeding Initiation in Nigeria

Abstract: This paper examined the general trend of timing of breastfeeding initiation among nursing mothers in Nigeria. The time of initiating the first breast milk to an infant by his/her mother is measured as whether it is immediate (before the first hour of birth) or delayed (after the first hour of birth), and the impacts of some socioeconomic and maternal factors on this are determined. Results from this study showed that mother's age at birth, her enhanced educational status, mothers' domiciling in urban areas, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 12 publications
2
19
1
Order By: Relevance
“…In the current study, we found higher rates of early initiation of breastfeeding among women who delivered at a healthcare facility compared with those who delivered at home. This is consistent with other studies conducted in Nigeria (Babatunde Yahya & Adebayo, 2013; Berde & Yalçin, 2016), Ethiopia (Horii et al, 2011), and Sri Lanka (Senarath et al, 2010) that had shown delivering in a healthcare facility to be positively associated with early breastfeeding initiation. Evidence from these studies suggests that the plausible reason behind the observed association would be the guiding role that health workers play in providing information to mothers on best practices about infant feeding, and the attribution of visible promotional communication about breastfeeding practice in the healthcare facilities (Petrova et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, we found higher rates of early initiation of breastfeeding among women who delivered at a healthcare facility compared with those who delivered at home. This is consistent with other studies conducted in Nigeria (Babatunde Yahya & Adebayo, 2013; Berde & Yalçin, 2016), Ethiopia (Horii et al, 2011), and Sri Lanka (Senarath et al, 2010) that had shown delivering in a healthcare facility to be positively associated with early breastfeeding initiation. Evidence from these studies suggests that the plausible reason behind the observed association would be the guiding role that health workers play in providing information to mothers on best practices about infant feeding, and the attribution of visible promotional communication about breastfeeding practice in the healthcare facilities (Petrova et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Other researchers have found a significant association between type of delivery and early breastfeeding initiation (Balyakina et al, 2016; Green, 2009). Factors such as discomfort after cesarean surgery, effects of anesthetics, and bonding issues between the mother and child have been associated with delayed initiation of breastfeeding (Babatunde Yahya & Adebayo, 2013; Balyakina et al, 2016; Green, 2009). Additionally, consistent with studies in Africa and other countries (Hazir et al, 2013; Örün et al, 2010; Pandey, Tiwari, Senarath, Agho, & Dibley, 2010), prelacteal feeding practices were negatively associated with initiating breastfeeding within 1 hr of birth in both rural and urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Although we found the type of birth to be significantly associated with EIBF in 1998 only, studies that assessed this association between 2013 and 2016 did not find it to be statistically significant in a multiple variable regression model. 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…Skilled delivery attendants that work in hospitals on the other hand, are formally trained, better understand the importance of early breastfeeding initiation, 44 and are consequently more likely to understand and adopt the Baby Friendly Health Initiative. This may explain the higher odds of early breastfeeding initiation among Nigerian women who gave birth in public hospitals versus their homes 34,45 found in our study. Skilled delivery providers like private and public hospitals are also more likely to better understand the concept of skin-to-skin contact at birth and are less likely to be influenced by traditional practices and cultural norms when compared to traditional birth attendants.…”
Section: Journal Of Global Health Reportsmentioning
confidence: 60%